Survivin a nádorová imunoterapie - Venhauerová, Anna (Jihočeská univerzita, 2018)
The main goal of this thesis was to study combination of our contemporary immunotherapy based on specific and nonspecific immunity with survivin inhibition. I studied molecular structure of survivin, his cellular localization, functions but in particular his targeting and blocking and possible positive and negative consequences on immune system and immunotherapy. Finally, I suggested possibilities of including survivin in our immunotherapy.
Survivin and cancer immunotherapy
Keywords: survivin; rakovina; nádorová terapie; survivin; cancer; immunotherapy